2015
DOI: 10.2174/1574884710666150812141525
|View full text |Cite
|
Sign up to set email alerts
|

Ability of older people with dementia or cognitive impairment to manage medicine regimens: a narrative review

Abstract: Impaired cognition has a significant impact on a person’s ability to manage their medicines. The aim of this paper is to provide a narrative review of contemporary literature on medicines management by people with dementia or cognitive impairment living in the community, methods for assessing their capacity to safely manage medicines, and strategies for supporting independent medicines management. Studies and reviews addressing medicines management by people with dementia or cognitive impairment published betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
81
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 62 publications
0
81
0
1
Order By: Relevance
“…Another consideration in weighing therapeutic options is that older adults with cognitive impairment may have greater difficulty adhering to a complex regimen of oral medications unless they have adequate caregiver support to assist with self-administration of medications. 27 …”
Section: Geriatric Assessmentmentioning
confidence: 99%
“…Another consideration in weighing therapeutic options is that older adults with cognitive impairment may have greater difficulty adhering to a complex regimen of oral medications unless they have adequate caregiver support to assist with self-administration of medications. 27 …”
Section: Geriatric Assessmentmentioning
confidence: 99%
“…Many studies of everyday functional ability, including those conducted in HIV and substance dependence (Blackstone et al, 2013; Sadek et al, 2007) have used self-report measures that ask the individual to rate how well they perform activities of daily living. We (Henry et al, 2010) and others (Elliott et al, 2015; Karagiozis et al, 1998; Patterson et al, 2001a) have proposed that reliance on self-report is problematic especially during the study of conditions with known cognitive impairment. Performance-based functional measures, such as the UCSD Performance Based Skills Assessment (UPSA-2), are useful in that they divide everyday function into specific components and have high reliability and validity (Patterson et al, 2001a; Patterson et al, 2001b), e.g., comprehension and planning abilities, financial skills, knowledge in use of transportation and managing the household, and the extent to which individuals can internalize and plan to take a complex daily regimen of medications.…”
Section: Introductionmentioning
confidence: 99%
“…There are a range of these tools available, and they can provide valuable information about patients' abilities to manage medications at the same time as identifying potential cognitive impairment. 3,4 A systematic review of these tools reported moderate to strong associations between performance on standardised medication management assessments and cognitive function. 3 Some medication management assessment tools were originally designed primarily for the purpose of screening for cognitive impairment, 5 since a decline in ability to manage medications may be an early sign of cognitive decline.…”
mentioning
confidence: 99%
“…3 Some medication management assessment tools were originally designed primarily for the purpose of screening for cognitive impairment, 5 since a decline in ability to manage medications may be an early sign of cognitive decline. 4 Standardised medication management assessment tools use either the patient's own medications or a mock medication regimen. They require the patient to perform various tasks such as read medication labels, remove medications from packaging and set out medications for the day.…”
mentioning
confidence: 99%
See 1 more Smart Citation